Clinical analysis and classification of placental abruption. (17th September 2021) - Qiu, Yu; Wu, Lixia; Xiao, Yunshan; Zhang, Xueqin
Abstract: Objective: To investigate the diagnosis, treatment, and maternal and fetal outcomes of placental abruption. Materials and methods: We recruited 585 cases of placental abruption from the Women and Children's Hospital Affiliated to Xiamen University between January 2012 and December 2017. Cases were categorized into four groups (class 0–III) according to the clinical guidelines published by the Obstetrics and Gynecology Branch of the Chinese Medical Association. We then compared clinical data and auxiliary examinations across the four groups. Results: The differences were statistically significant ( p  < .01) among the four groups of placental abruption with regard to the incidence of an abnormal ultrasound finding. Positive ultrasound signs were evident in 6.4% of the patients categorized as class 0 and 100.0% of patients categorized as class III. Monitoring showed that fetal heart rate (FHR) was abnormal in class II patients with placental abruption; patients in class III showed no fetal heart sounds. Cesarean section was carried out for 26.6%, 75.1%, 65.2%, and 47.1% of patients in classes 0, I, II, and III, respectively. The rate of cesarean section for classes I and II was the highest, while the lowest rate occurred for class 0. Postpartum hemorrhage occurred in 2.5%, 9.3%, 15.2%, and 29.4% of patients across the four groups, DIC occurred in 0.0%, 1.3%, 2.3%, and 23.5% of cases, and perinatal death occurred in 1.0%, 1.3%, 7.6%, and 100.0% of cases, respectively. The highest incidence of postpartum hemorrhage was in class III (29.4%) and the lowest was in class 0 (2.5%). The highest incidence of DIC was in class III (23.5%) and the lowest was in class 0 (0.0%). The highest incidence of neonatal asphyxia was in class II (34.1%) and the lowest was in class 0 (10.1%). Regarding perinatal death, the highest incidence was in class III (100.0%) and the lowest was in class 0 (1.0%). These data showed significance differences when compared across the four groups of patients ( p  < .01). Conclusions: We recommend that the diagnosis of placental abruption should consider risk factors, clinical features, FHR monitoring, and dynamic ultrasound monitoring. Early diagnosis and treatment can improve maternal and infant prognosis.